1984
DOI: 10.1109/jssc.1984.1052216
|View full text |Cite
|
Sign up to set email alerts
|

Low power dissipation MOS ternary logic family

Abstract: An MOS ternary-logic family is proposed, which is comprised of a set of inverters, NOR gates, and NAND gates. These gates are used to design basic ternary arithmetic and memory circuits. The circuits thus obtained are then used to synthesize complex ternary arithmetic circuits and shift registers. The ternary circuits developed are shown to have some significant advantages relative to other known ternary circuits like low power dissipation, and reduced propagation delay and component count. For a given dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(76 citation statements)
references
References 11 publications
0
72
0
1
Order By: Relevance
“…The output of this ternary inverter is defined by a equation. In a ternary inverter, if i is the input and three outputs are a, b and c, then they can be obtained from these three equations [16], [17] which are given below: table given in TABLE 1 and TABLE 2 [14], [16], [17].…”
Section: Ternary Not Gate/invertermentioning
confidence: 99%
“…The output of this ternary inverter is defined by a equation. In a ternary inverter, if i is the input and three outputs are a, b and c, then they can be obtained from these three equations [16], [17] which are given below: table given in TABLE 1 and TABLE 2 [14], [16], [17].…”
Section: Ternary Not Gate/invertermentioning
confidence: 99%
“…Ternary logic (or three-valued logic) has attracted considerable interest due to its potential advantages over binary logic for designing digital systems. For example, it is possible for ternary logic to achieve simplicity and energy efficiency in digital design since the logic reduces the complexity of interconnects and chip area [19]. Furthermore, serial and serial-parallel arithmetic operations can be carried out faster if the ternary logic is employed.…”
Section: Ternary Logic Gate Design Using Cntfetmentioning
confidence: 99%
“…Furthermore, serial and serial-parallel arithmetic operations can be carried out faster if the ternary logic is employed. Extensive research on design and implementation of ternary logic using CMOS can be found in the technical literature [19,20]. Chip area and power dissipation can be reduced by more than 50% using an efficient MVL implementation for a signed 32-bits multiplier compared to its fastest binary counterpart [11].…”
Section: Ternary Logic Gate Design Using Cntfetmentioning
confidence: 99%
“…Multiple Valued logic (MVL) such as Ternary logic is considered over binary logic due to its considerable advantages such as reduced interconnects, chip area [3], faster serial, serial-parallel arithmetic operations. MVL logic enhances the performance of CMOS technology in the logic design [6].…”
Section: Introductionmentioning
confidence: 99%